Dynorphin-κ-opioid receptor signaling, but not µ-opioid receptor signaling, partly mediates the suppression of luteinizing hormone release during late lactation in rats. (20th November 2022) - Tsuchida, Hitomi; Nonogaki, Miku; Inoue, Naoko; Uenoyama, Yoshihisa; Tsukamura, Hiroko
Highlight: Dynorphin mediates the suppression of LH pulses during late lactation. β-endorphin-µ-opioid receptor signaling doesn't mediate the suppression. PVN and SON dynorphin neurons are activated by suckling stimulus. Abstract: Follicular development and ovulation are profoundly suppressed during lactation. This suppression is suggested to be due to the suckling-induced inhibition of the kisspeptin gene (the master regulator of reproduction) in the arcuate nucleus (ARC) and subsequent inhibition of pulsatile gonadotropin-releasing hormone (GnRH)/gonadotropin release. The present study examined whether hypothalamic κ-opioid receptor (KOR) or µ-opioid receptor (MOR) signaling mediates the suppression of luteinizing hormone (LH) release induced by suckling stimulus during late lactation in rats. Central administration of a selective KOR antagonist blocked the suppression of LH release on Day 16 of lactation; however, central administration of a selective MOR antagonist failed to block the suppression. The suckling stimulus significantly increased the number of fos (a marker for neural activation)-positive Pdyn (dynorphin gene)-expressing cells in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) but not in the ARC. Taken together, these results suggest that central KOR signaling, but not MOR signaling, at least partly, mediates the suppression of LH release induced by suckling stimulus during late lactation, and PVN and SON Dyn neurons may be involved in the suppression in rats.